Penentuan Prioritas Penerima Bantuan Fisik Gedung Sekolah Menengah Atas di Kabupaten Madiun Jawa Timur dengan Metode Weighted Sum Model - Rochidajah Rochidajah; Pradityo Utomo (Journal of Information Technology Ampera, 2022)
Education is the main need of every society in Indonesia. One of the factors supporting education is the availability and physical feasibility of the building. Problems that often occur include inadequate building conditions and the ratio of the building to the number of students. This problem can be exacerbated by the unfair provision of physical assistance for school buildings. This study discusses how to prioritize physical assistance for school buildings, especially in Senior High Schools, Madiun Regency, East Java. Madiun Regency has 13 Senior High Schools located in the highlands and lowlands. The provision of building physical assistance is expected to be fair by referring to several parameters, including the number of students, the number of teachers, the number of classrooms, the number of laboratories, the number of libraries, and land area. These parameters are used as the criteria for the priority decision support system for high school physical assistance using the computer-based Weighted Sum Model method. From this research, it can provide results in the form of recommendations for priority high schools in Madiun Regency to get physical building assistance.